EVALUATION OF SOYBEANS AS A PREDECESSOR FOR WINTER WHEAT IN THE WESTERN FOREST-STEPPE OF UKRAINE - Lykhochvor В.; Ivaniuk В.; Bliatnyk Т.; Salikov Д. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The value of soybeans as a predecessor for winter wheat was assessed through field and laboratory studies conducted on dark gray podzolized soil at the research field of the Department of Crop Technologies of Lviv National Environmental University. Four predecessors were studied: fallow, wheat, sunflower, and soy. After harvesting the predecessors, the moisture content and different forms of nitrogen in the soil were determined. The yield of winter wheat after these predecessors was also determined, allowing the researchers to establish the value of predecessors for winter wheat. Before sowing wheat, the moisture reserve was lowest after soybean (125.6 mm) and highest after sunflower (139.1 mm). The analysis showed that the difference in soil moisture content after different predecessors is relatively insignificant. These indicators suggest that in areas with sufficient moisture, it is rarely a limiting factor in wheat productivity. The study’s authors found that soybeans absorb a significant amount of nitrogen from the soil to produce high-protein grain. After soybean harvest, the nitrate nitrogen content in the soil is low. In dark gray forest soil, with a soybean yield of more than 3 t/ha, the nitrate nitrogen content is 13.6 mg/kg of dry soil, which is insufficient for the active growth of winter wheat in the autumn and spring growing seasons. In comparison, the nitrate content after wheat and sunflower during the same period was higher by 5.9 and 7.8 mg/kg, respectively. Semi-fallow cultivation of the soil results in the highest nitrate content of 34.1 mg/kg, almost three times more than the predecessors of soybeans. The highest yield of winter wheat was observed when being planted after semi-fallow cultivation, reaching 8.38 t/ha. In the Western Forest-Steppe conditions, soybeans were found to be the worst predecessors, with a yield of winter wheat after soybeans of only 7.80 t/ha. The yield of wheat after sunflower was 0.24 t/ha higher than after soybean. Even with monoculture wheat cultivation, wheat yields were 0.08 t/ha higher than after soybeans. The relatively small difference in productivity depending on the predecessors can be explained by the application of a large amount of mineral fertilizers - N60+80+40Р60К90, which neutralized the influence of the predecessors.